2018
DOI: 10.31557/apjcp.2018.19.12.3629
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognosis of Spontaneously Ruptured Hepatocellular Carcinoma in Thailand

Abstract: Objective: Hepatocellular carcinoma (HCC) is the fatal cancer worldwide. Spontaneously Rupture remains important complication of HCC. The incidence of spontaneous HCC rupture was high in ASEAN but limited studies were reported. The aim of this study was to evaluate predictors and overall survival of ruptured HCC in tertiary care center in Thailand. Methods: We conducted a retrospective cohort study of HCC patients aged ≥15 years old during January 2012-January 2016 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
1
17
0
5
Order By: Relevance
“…Higher α-FP had contributed to the risk of rHCC in this study. This result does support similar findings regarding α-FP from another retrospective study on rHCC [ 6 ]. However, increasing serum concentrations of α-FP may also be correlated with larger tumor size [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher α-FP had contributed to the risk of rHCC in this study. This result does support similar findings regarding α-FP from another retrospective study on rHCC [ 6 ]. However, increasing serum concentrations of α-FP may also be correlated with larger tumor size [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a nationwide study from Japan and a retrospective study from Thailand, ascites has been shown to be an independent risk factor of rHCC. However, the explanations of why HCC with ascites is more likely to rupture are still questionable [ 2 6 16 ]. Higher α-FP had contributed to the risk of rHCC in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al 7 in a retrospective study of 4209 patients with HCC had 200 with rupture and found that hypertension, cirrhosis, tumor size >5 cm, tumor protrusion outside the surface, and extra-hepatic invasion were predictive factors of rupture. Kerdsuknirun et al 34 in 51 ruptured cases out of 333 HCC patients found that age, abdominal pain, anemic symptoms, and Child-Pugh score more than 6 were independent predictive factors of ruptured HCC. Many of the studies on ruptured HCC are from large cohorts in Asia, which are quite homogenous, with viral hepatitis B and C as the main etiology of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conservative treatment can improve the general situation of patients to a certain extent, but its effect is not ideal. So, it is recommended that simple conservative treatment is only suitable for dying patients with poor liver function and locally advanced tumors who cannot tolerate transcatheter arterial embolization (TAE) or surgery (39,(55)(56)(57).…”
Section: ) Conservative Treatmentmentioning
confidence: 99%